(untitled) (A Social Science and Entrepreneurship Journal, 2025)
This article discusses the role of innovation, proactivity, and risk-taking courage as key factors in building and managing a business in the midst of the challenges of the era of Received 1 Feb 2025 Revised 1 Mar 2025 Accepted 20 Mar 2025 Available online 1 April 2025 globalization and increasingly fierce economic competition. Using a case study of AFD Collection, a fashion business that successfully survived and thrived during the COVID-19 pandemic, this article reviews how implementing product innovation, digital marketing strategies, and adapting to market changes can support business continuity and growth. In addition, this article also explores the importance of effective human resource management, optimization of digital technology to improve operational efficiency, and careful planning in dealing with market dynamics. The findings in this article provide strategic insights and practical advice for entrepreneurs, especially in the face of uncertainty and challenges in volatile global markets, so as to strengthen their